Invisible giants : the empires of Cleveland's Van Sweringen brothers - Harwood, Herbert H. (Indiana University Press, 2003)
Invisible Giants is the Horatio Alger-esque tale of a pair of reclusive Cleveland brothers, Oris Paxton and Mantis James Van Sweringen, who rose from poverty to become two of the most powerful men in America. They controlled the country's largest railroad system a network of track reaching from the Atlantic to Salt Lake City and from Ontario to the Gulf of Mexico. On the eve of the Great Depression they were close to controlling the country's first coast-to-coast rail system a goal that still eludes us. They created the model upper-class suburb of Shaker Heights, Ohio, with its unique rapid tr.